2020
DOI: 10.1038/s42003-020-01306-4
|View full text |Cite|
|
Sign up to set email alerts
|

VEGFC negatively regulates the growth and aggressiveness of medulloblastoma cells

Abstract: Medulloblastoma (MB), the most common brain pediatric tumor, is a pathology composed of four molecular subgroups. Despite a multimodal treatment, 30% of the patients eventually relapse, with the fatal appearance of metastases within 5 years. The major actors of metastatic dissemination are the lymphatic vessel growth factor, VEGFC, and its receptors/co-receptors. Here, we show that VEGFC is inversely correlated to cell aggressiveness. Indeed, VEGFC decreases MB cell proliferation and migration, and their abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
(81 reference statements)
1
9
0
Order By: Relevance
“…The concept of vasculogenic mimicry corresponds to vessel-like formation by endothelial cells or some tumour cells that exhibit invasive capacity [ 53 , 54 ]. Daoy, ONS-76, and HD-MB03 cells were able to organize as pseudo-vessels [ 55 ], and D341Med cells were unable to do so.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of vasculogenic mimicry corresponds to vessel-like formation by endothelial cells or some tumour cells that exhibit invasive capacity [ 53 , 54 ]. Daoy, ONS-76, and HD-MB03 cells were able to organize as pseudo-vessels [ 55 ], and D341Med cells were unable to do so.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, any treatment that can induce the death of tumour cells that have survived multiple cycles of radiation is an important breakthrough. To test the relevance of C29 after relapse, we generated radiation-resistant Daoy and HD-MB03 cells to simulate relapse after radiotherapy [ 55 ]. Two independent populations were generated for each cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that VEGF‐C system plays neurotrophic roles in neural development [ 11 , 12 , 32 ] and neurological diseases, such as ischemia [ 13 , 33 , 34 , 35 ], brain tumor [ 36 , 37 , 38 ], and Alzheimer's disease [ 39 ]. In patients with epilepsy and animal models, VEGF‐C and its receptors were found to be upregulated in the epileptogenic foci [ 15 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, tumor cells also use lymphatic vessels to migrate and metastasize, which has implications for treatments. Interestingly, the main lymphatic endothelial cell growth factor VEGFC, which promotes the sprouting of lymphatic vessels, has been associated with anti-tumoral effects in MB [ 164 ]. This indicates that the lymphatic system might be beneficial in preventing MB growth as opposed to the current understanding in other cancers.…”
Section: Targeting the Brain Tumor Vasculature In Medulloblastomamentioning
confidence: 99%